2021
DOI: 10.1016/j.isci.2021.102654
|View full text |Cite
|
Sign up to set email alerts
|

Porous TiO2 thin film-based photocatalytic windows for an enhanced operation of optofluidic microreactors in CO2 conversion

Abstract: HighlightsPhotocatalytic windows provide enhanced operation of optofluidic microreactors Use of TiO 2 nanometric coatings reduces the required photocatalyst amountThe robustness of the coating implies stability upon long-working periods CO 2 -to-CH 3 OH conversion performance is related to the porosity and crystallite size

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Photocatalytic activity depends on the ability of the catalyst to absorb light and create electron-hole pairs (Angulo-Ibanez et al, 2021). Broadening the wavelength range of light that the catalyst can absorb, increasing the intensity of light absorption, and promoting the separation of electron-hole pairs are the common approaches to improve the performance of photocatalysts.…”
Section: Photocatalytic Co 2 Rrmentioning
confidence: 99%
“…Photocatalytic activity depends on the ability of the catalyst to absorb light and create electron-hole pairs (Angulo-Ibanez et al, 2021). Broadening the wavelength range of light that the catalyst can absorb, increasing the intensity of light absorption, and promoting the separation of electron-hole pairs are the common approaches to improve the performance of photocatalysts.…”
Section: Photocatalytic Co 2 Rrmentioning
confidence: 99%
“…12 TiO 2 has excellent photostability and is environmentally friendly and has become one of the most popular photocatalysts. [13][14][15] Angulo-Ibáñez et al 16 used a porous TiO 2 film base to effectively reduce the amount of TiO 2 used while still maintaining high CO 2 to CH 3 OH conversion performance. Albo et al 17 synthesized a Mo 2 C/ TiO 2 heterojunction catalyst via a carbothermal method, which showed high stability and recyclability under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Albo and Garcia [285] evaluated the efficacy of a photoresponsive MO 2 C/TiO 2 blend in converting CO 2 gas to methanol using a micro-optofluidic reactor that operated under UV and visible light. They reported that the presence of MO 2 C may extend the spectrum response and lower the recombination rate of photogenerated electrons in titanium dioxide, resulting in a stable synthesis of methanol at 4 wt % MO 2 C. Angulo-Iba ´n ˜ez et al [286] investigated the effect of creating a photocatalytic window to enhance the optofluidic microreactor performance. The window consisted of a mesoporous anatase layer as the outer layer and a TiO 2 layer as the internal protective layer.…”
Section: Homogeneous Reactions In Microreactorsmentioning
confidence: 99%